Intentional Presentation of Objects in Cooperatively Breeding Arabian Babblers (Turdoides squamiceps) - Ben Mocha, Yitzchak; Pika, Simone (Frontiers in Ecology and Evolution, 2019)
The emergence of intentional communication and the intentional presentation of objects have been highlighted as important steps in the ontogeny of cooperative communication in humans. Furthermore, intentional object presentation has been suggested as an extremely rare form of communication evolutionarily. Research on comparable means of communication in non-human species may therefore shed light on the selection pressures that acted upon components of human communication. However, the functions and cognitive mechanisms that underlie object presentation in animals are poorly understood. Here, we addressed these issues by investigating object presentations in wild, cooperative breeding Arabian babblers (Aves: Turdoides squamiceps). Our results showed that individuals presented objects to specific recipients. The recipients most often responded by approaching the signaler and the dyad then moveed jointly to copulate at a hidden location. We provide evidence that object presentations by Arabian babblers (i) do not represent a costly signal, as objects were not costly to acquire; (ii) were not used to trade food for sex, as the presentation of food was not more likely to result in copulation; and (iii) possessed hallmarks of first-order intentionality. These results show that intentional presentation of objects is not restricted to the primate linage and may suggest that the need to engage in cooperative interactions facilitates elaborate socio-cognitive performances.